‘We don’t have blasphemy laws in England.’ What does this mean for RE? - Marshall, Heather (Journal of Religious Education, 2024)
The protection and regulation of religious expression present complex challenges. Blasphemy laws, which criminalize acts deemed disrespectful to religious beliefs, have been abolished in England, allowing for broader freedom of expression. However, concerns and discussions about blasphemy persist. The Home Secretary, Suella Braverman (2023), has emphasized that there are no blasphemy laws in Great Britain and no obligation to show reverence towards any religion. Religious Education (RE) plays a crucial role in fostering understanding and tolerance of diverse religious traditions. It provides students with opportunities to develop critical thinking skills and engage in meaningful dialogue. However, certain aspects of critical thinking within RE may be perceived as provocative or blasphemous. This paper explores the ongoing debate on blasphemy laws in England, considering the evolving religious landscape and its implications for the teaching of RE. It aims to shed light on the complex dimensions of this discourse.